2021
DOI: 10.3390/f12040432
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature on Anoplophora chinensis (Coleoptera: Cerambycidae) Adult Survival, Reproduction, and Egg Hatch

Abstract: Anoplophora chinensis (Forster) is an invasive species that can damage many tree species in orchard, urban, and forested habitats. Adult survival, reproduction, and egg hatch of A. chinensis from Italy and China are evaluated at eight constant temperatures (5, 10, 15, 20, 25, 30, 35, and 40 °C) under laboratory conditions. The estimated Tmax for longevity was 42 and 33 °C for females and 42 and 39 °C for males from China and Italy, respectively. The estimated Tmax, Tmin, and optimum temperature for fecundity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…For example, the elytra of ALB adults are marked with white spots in some populations but yellow in other populations in China and the original yellow type Anoplophora nobilis (Ganglbauer) was considered as a synonym ALB (white type) as cross-mating experiments between these two types yielded viable offspring and intermediate colors of the patches of setae on the elytra of the hybrid offspring adult [55]. Recent studies also showed a difference in thermal responses between A. chinensis and A. malasiaca [48,56]. Despite these differences, our results first confirm that A. malasiaca is reproductively compatible with A. chinensis (i.e., considered as one biological species).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the elytra of ALB adults are marked with white spots in some populations but yellow in other populations in China and the original yellow type Anoplophora nobilis (Ganglbauer) was considered as a synonym ALB (white type) as cross-mating experiments between these two types yielded viable offspring and intermediate colors of the patches of setae on the elytra of the hybrid offspring adult [55]. Recent studies also showed a difference in thermal responses between A. chinensis and A. malasiaca [48,56]. Despite these differences, our results first confirm that A. malasiaca is reproductively compatible with A. chinensis (i.e., considered as one biological species).…”
Section: Discussionmentioning
confidence: 99%
“…The two CLB populations were imported in 2018 under permit from EBCL. The Italian individuals used were from the 16th, 17th, or 18th laboratory generations and the Chinese individuals were from the 6th or 7th laboratory generations [48]. Molecular analysis of the invasive Italian population indicates its origin from Japan and that it is part of what was previously called A. malasiaca prior to the revision of this genus [11,22].…”
Section: Insectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The citrus long-horned beetle Anoplophora chinensis (Forster) and the gypsy moth Lymantria dispar L., for example, are both invasive, destructive pests which can damage many tree species in orchard, urban, and forested habitats. Hence, information on temperature requirements of the citrus long-horned beetle, and on the key traits affecting the gypsy moth's dispersal capability, are provided in order to develop phenological models for management or eradication efforts [10,11]. Specifically, Keena et al [10] evaluated adult survival, reproduction, and the egg hatching of A. chinensis at eight constant temperatures under laboratory conditions; these can be used to predict the timing of stages.…”
mentioning
confidence: 99%
“…Hence, information on temperature requirements of the citrus long-horned beetle, and on the key traits affecting the gypsy moth's dispersal capability, are provided in order to develop phenological models for management or eradication efforts [10,11]. Specifically, Keena et al [10] evaluated adult survival, reproduction, and the egg hatching of A. chinensis at eight constant temperatures under laboratory conditions; these can be used to predict the timing of stages. Srivastava [11], in addition, provided a review of the current literature on the variations in flight capability and flight distance of gypsy moth populations for each subspecies, as well as shifts in other traits of concern.…”
mentioning
confidence: 99%